The Middle Paleolithic from Mujina Pećina, Dalmatia, Croatia - Karavanić, Ivor (Array, 2008)
Mujina Pećina in Dalmatia, Croatia is the only systematically excavated and well dated Middle Paleolithic cave site in the eastern Adriatic. Its stratigraphic sequence covers the period between 45 and 39 uncalibrated ka. Results of sedimentological, lithic, faunal and paleobotanical analyses of the upper levels (levels B, C, D1 and D2) show that this was a hunting site only sporadically visited by humans. During these occupation episodes humans processed animal remains (mostly large bovids, cervids, and caprids) and produced tools from the locally available raw material. Carnivore use of the cave is also indicated, particularly in the upper levels. This work contributes to our understanding of lifestyle and mobility patterns of the Middle Paleolithic inhabitants of this region.